Safety, occupational health and risk management in construction projects in pandemic COVID 19 - Vargas Charaja, Edinson Junior (2021)
The evaluation of the occupational health and safety management systems was carried out to mitigate risks in construction projects in the Tacna region in a COVID-19 pandemic situation. For this purpose, the techniques for data collection used in the methodology; working on four construction projects in the Tacna region were the opinion of professionals in the construction sector, the analysis of documents and information on each project and the quantitative analysis of risk factors. Similarly, among the instruments used, there were forms, the projects’ technical sheets, statistical graphs, hazard identification and risk assessment matrices (IPER), the Jack Knife graph, and the basic guidelines check list of a system of occupational health and safety management. The results indicate that the occupational health and safety management system to mitigate risks was adequately implemented, observing a moderate negative impact. In addition, in terms of basic gu